39.8k views
3 votes
Which expressions are equivalent to − 6 + 3 ( 2 + ( − 4 t ) ) −6+3(2+(−4t))minus, 6, plus, 3, left parenthesis, 2, plus, left parenthesis, minus, 4, t, right parenthesis, right parenthesis ?

2 Answers

2 votes

Answer:

-12t

Explanation:

User Warre Buysse
by
5.9k points
3 votes

Answer:

-12t

Explanation:

Given the expression − 6 + 3 ( 2 + ( − 4 t ) ), to get the equivalent expression, the following steps must be followed;

Step 1: Multiply the signs inside the parenthesis

= − 6 + 3 ( 2 + ( − 4 t ) )

= -6+3(2-4t)

Step 2: Open up the parenthesis

= -6 + 3(2)+3(-4t)

= -6 + 6 - 12t

Step 3: Simplify the resulting expression by taking the diffrence between -6 and 6:

= 0 - 12t

= -12t

Hence the equivalent expression is -12t

User Kashif Jilani
by
5.0k points